On Continuity and Readiness for Education: Methodology Principles of Quality-Based System Management After Helen N. Solovova - N. E. Bulankina (Дискурс профессиональной коммуникации, 2021)
This paper is devoted to the analysis of the most crucial problems related to innovative trends in modern education, i.e. increasing competitiveness. The aim of this paper is twofold: a) to consider the phenomenon of current methodology of professional education in terms of international principles ISO depicted in the research works of the outstanding methodologist and educator, Professor Helen N. Solovova; b) to reveal the versatility of the scientist’s activities in the frameworks of current academic scholarship. The main methodological concept considers the global strategic processes, and the value orientations of educational activity which become especially significant for those who have to work with a personality; the latter has to understand the realia of continuing transformations of the society, qualitative and quantitative changes in the educational environment of the country and the regions, and rather ambiguous social, informational, and educational aspects of the information spaces. As a result of this study, we state that current challenges are of prior importance for the personality development as individuality. As a priority this concerns a constantly changing status of education as a whole, and the image of the university and college trainers, school educators and tutors at In-Service institutions; as is the case, these phenomena reflected in both Russian and International Scientific Scholarship help to understand the progressive methodology principles which cover Knowledge Content, Technology, and Pedagogy/Language Didactics. In conclusion, a special role, for sure, belongs to the methodology of teaching foreign languages (H.Solovova’s concept of prior significance), which performs a humanizing and cultural mission; language pedagogy and didactics are in search of novel principles and approaches to the philosophy of training and learning foreign languages as a valuable intellectual component of Russian culture and education as a whole.